EL METADISCURSO DESCRIPTIVO EN LOS RELATOS DE THÉOPHILE GAUTIER - Pardo Jiménez, Pedro (Anales de Filología Francesa, 2007)
A painter and art critic, Théophile Gautier createsa preeminently visual aesthetics that, in his literary oeuvre, renders description a truly overwhelming presence. On this basis, the author is forced to resolve the dialectics between the antagonistic forces of narrative progress (demanded by the needs of the short story) and descriptive suspension (demanded by his own expressive needs). Of the techniques Gautier employs to inscribe description into his narratives, the most original is a type of descriptive metadiscourse which, in the course of his evolution as a writer, develops from a reflection on the art of writing into a legitimation of descriptive excess.